Modelling the Database Development for Waqf Land in District of Melaka Tengah Malaysia - Halim, Mohd Badiulzaman Bin Mohamed Abdul; Borhan, Halimahton; Hitam, Mizan; Kamaruddin, Siti Mazwin (Business Management and Strategy, 2024)
The development of waqaf land database is an agenda that is increasingly given significant attention by the agency or institution around the world as that is the driving force to improving for management dan administation waqaf land. However, waqaf institutions have not yet been seen as institutions that can solve the management and administration problems of waqaf land. This is because there are problems in terms of registration and good procedures including in the State of Malacca. This study will comprehensively look at the waqaf system according to the latest technological developments such as the use of Geographic Information System (GIS) software. The method of interviewing those who are directly involved with waqf institutions, namely Majlis Agama Islam Melaka (MAIM) officials, land administrators at land officers and local authority officials has been conducted. In addition, site visits are also carried out on waqaf land or buildings. The results of the study shows that many data and documents related to waqaf are incomplete and not updated as they should be. MAIM is facing difficulties in developing its waqaf land due to the problem. Finally, this study presents some suggestions that can help strengthen the management and administration of MAIM such as prioritizing the waqaf land database system like the use of Mapinfo software for recording purposes. It can only be achieved if the lack of integration, lack of coordination and waqaf procedures can be overcome, then waqaf land registration can be collected and consolidated.